2024
DOI: 10.1039/d3sc06456e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-directed bimodal crystallization of the quasi-1D van der Waals phase, Bi4I4

Steven Jay Allison,
Dmitri Leo Mesoza Cordova,
Maham Hasib
et al.

Abstract: Anisotropy often yields unexpected structures and properties in the solid state. In van der Waals (vdW) solids comprised of 1D or quasi-1D (q-1D) building blocks, anisotropy in both intra- and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The case of the Sn(Br/I)P crystals suggests that the propagation of crystallographic screw axes along the long-axis of weakly bound chains leads to helical structures. ,,, Encouragingly, the immense interest in exfoliable 1D crystals has sparked the search for classes of inorganic crystals with sub-nanometer-thick chains held by vdW interactions. Thus, the identification of screw axis symmetry within emergent 1D vdW crystal classes led to our discovery of helical motifs in III–VI–VII 1D vdW crystals (III = Al, Ga, In; VI = S, Se, Te; VII = Cl, Br, I). ,,,, We found that crystals in this class manifest tetrahelical motifs along chains held by vdW interactions. ,,, For example, InSeI is a semiconductor consisting of periodic helical chains defined by a 4 1 screw axis and shows highly temperature-sensitive bandgaps in the visible range (Figure S1). ,,, Substitution of Ga atoms to the In site led to GaSeI, which is the first freestanding inorganic tetrahelix that is an approximate Boerdjik–Coxeter (B–C) helix .…”
mentioning
confidence: 99%
“…The case of the Sn(Br/I)P crystals suggests that the propagation of crystallographic screw axes along the long-axis of weakly bound chains leads to helical structures. ,,, Encouragingly, the immense interest in exfoliable 1D crystals has sparked the search for classes of inorganic crystals with sub-nanometer-thick chains held by vdW interactions. Thus, the identification of screw axis symmetry within emergent 1D vdW crystal classes led to our discovery of helical motifs in III–VI–VII 1D vdW crystals (III = Al, Ga, In; VI = S, Se, Te; VII = Cl, Br, I). ,,,, We found that crystals in this class manifest tetrahelical motifs along chains held by vdW interactions. ,,, For example, InSeI is a semiconductor consisting of periodic helical chains defined by a 4 1 screw axis and shows highly temperature-sensitive bandgaps in the visible range (Figure S1). ,,, Substitution of Ga atoms to the In site led to GaSeI, which is the first freestanding inorganic tetrahelix that is an approximate Boerdjik–Coxeter (B–C) helix .…”
mentioning
confidence: 99%